2014
DOI: 10.1007/s11356-014-3929-x
|View full text |Cite
|
Sign up to set email alerts
|

A 3-year study on occurrence of emerging contaminants in an urban stream of São Paulo State of Southeast Brazil

Abstract: This manuscript reports a 3-year study on occurrence of pharmaceuticals, hormones, and triclosan in surface waters of a central urban region of São Paulo State of Southeast Brazil (the Monjolinho River in São Carlos). Water samples collected once at every 2 months were pre-concentrated by solid-phase extraction (SPE) and analyzed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). The most frequently detected compounds in higher concentrations were caffeine, paracetamol, and atenolol (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(77 citation statements)
references
References 70 publications
5
50
1
21
Order By: Relevance
“…Além destes, a progesterona e a testosterona são exemplos de outros hormônios naturais que, assim como os estrogênios, são excretados diariamente pela urina e podem ser determinados nos corpos d'água que recebem grandes aportes de esgoto doméstico. 7,9,18,[20][21][22][23][40][41][42]46,[51][52][53][54] Os estrogênios sintéticos, encontrados em produtos farmacêuti-cos, são esteróides que tiveram suas estruturas moleculares alteradas. Os principais usos estão relacionados aos contraceptivos, terapias de reposição hormonal e tratamento de neoplasias.…”
unclassified
“…Além destes, a progesterona e a testosterona são exemplos de outros hormônios naturais que, assim como os estrogênios, são excretados diariamente pela urina e podem ser determinados nos corpos d'água que recebem grandes aportes de esgoto doméstico. 7,9,18,[20][21][22][23][40][41][42]46,[51][52][53][54] Os estrogênios sintéticos, encontrados em produtos farmacêuti-cos, são esteróides que tiveram suas estruturas moleculares alteradas. Os principais usos estão relacionados aos contraceptivos, terapias de reposição hormonal e tratamento de neoplasias.…”
unclassified
“…The value found in the present work is similar to that found in the River Thames (London, United Kingdom), in which the authors described that CAF was present at the concentration of 112 ng/L (Munro et al ). However, this value is lower than those found in the Monjolinho River and the Água Quente stream located in São Paulo state, São Carlos city (Brazil) (average of 15 000 ng/L) (Campanha et al ).…”
Section: Resultsmentioning
confidence: 64%
“…For example, in Minas Gerais, the average concentration of 17α-ethinylestradiol in waters nearby the capital, Belo Horizonte, is 206 ng/L, considering 15 positive data (34 % of the total) 46,47 . In the region of São Carlos (São Paulo), Campanha et al 39 reported an average value of 2 ng/L for 17β-estradiol in 24 positive data out of a total of 81 (30 %). Again, these results demonstrate the great variability of Brazilian surface waters concerning their degree of pollution, certainly influenced by sewage discharges, as pointed out earlier 1,42,60 .…”
Section: Resultsmentioning
confidence: 99%